Macroeconomic accounts: an overview - Host-Madsen, Paul (Washington, D.C. International Monetry Fund, 1979)
This pamphlet is aimed at meeting the need for a short and relatively simple exposition of the principles underlying macroeconomic statistics, viewed as an integrated whole.
International Monetary Fund: no. 29
Including bibliographical references
osa 22/10/19
Loans
Keywords: Macroeconomics; National income; Accounting; Balance of payment; Flow of funds